Impact of first COVID‐19 lockdown on paediatric and adult haemophilia patients treated in a French Haemophilia Comprehensive Care Centre. Issue 3 (3rd March 2022) - Volot, Fabienne; Soudry‐Faure, Agnes; Callegarin, Anamaria; Ksiazek, Eléa; Delienne, Stephanie; Cottin, Yves; Maynadié, Marc; Boulin, Mathieu
Abstract: Introduction: The coronavirus disease 2019 (COVID‐19) pandemic has created an unprecedented global health crisis. Aim: To investigate the impact of the 1 st COVID‐19 lockdown on haemophilia patients in terms of symptoms, management, medication adherence, mental health and lifestyle behaviours. Methods: A prospective cross‐sectional phone survey using a two‐part questionnaire was conducted in haemophilia patients (adults and children) followed‐up in a French Haemophilia Comprehensive Care Centre between May 5, 2020 and June 2, 2020 (CLEO CD study: NCT04390126). Results: Among 284 haemophilia A or B patients with FVIII or FIX < 40% contacted for the study, 239 (84%) including 183 adults and 56 children participated to the survey. In 81% of children and 78% of adults, bleeding episodes remained unchanged or decreased. Medication adherence was 82.0% in adults and 98.2% in children. Non‐adherence concerned haemostatic agents in six patients and analgesics in three. Overall, 67% of adults and 71% of children felt as good as before lockdown. In both adults and children, the three major changes in lifestyle behaviours were: increase in screen time (49% and 57%), decrease in physical activity (43% and 48%), and weight gain (32% and 27%), respectively. Conclusions: Encouraging results were observed in terms of haemophilia symptoms, medication adherence, and mental health. Conversely, a negative impact was observed on lifestyle behaviours in a cohort of French haemophilia patients during the 1 st lockdown.